China’s soft power and its cultural implication for Sri Lanka: Exploring Students’ perspectives - Jayasundara, Jayani (My University, 2023)
As China is now influential in most aspects of international politics, it has found a means to enhance and strengthen its influence peacefully. China’s relations can be seen in almost every region in the world, particularly in Southeast Asia, Africa, Latin America, and Central Asia to enhance its influence in these regions and to project itself as a benign nation. Last decade it has rapidly expanded into the South Asian countries following an integrated strategy of economic engagement, development assistance, and cultural exchanges. Chinese initiatives in all these respects in the region have expanded through the concept of soft power. The Soft power initiative now became an increasingly important role in Chinese foreign policy strategies. China’s growing presence in Sri Lanka as a south Asian country can be seen notably through the soft power initiative. This study examines the China’s growing presence in Sri Lanka in Cultural, Economic and Public diplomacy. The main focus of this study is to identify the implications of cultural diplomacy as a soft power tool. Therefore, as the study population, the present study has selected the University students of Sri Lanka. A judgmental sampling had been performed to collect the data with a structured questionnaire. The method employed for the data collection was quantitative and a correlational exploratory research design. The study reveals, there is a strong relationship between the influencing factors and the China’s soft power. All three sub-dimensions, Cultural diplomacy, Economic diplomacy and Public diplomacy were jointly and individually influencing Sri Lanka as the Soft power tools. Necessary recommendations were identified to increase the level of diplomatic relations between the two countries.
Keywords: China’s Soft Power, Cultural diplomacy, Economic Diplomacy, Public Diplomacy, Sri Lanka.